2017
DOI: 10.1002/2017jd026987
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Impact of Calbuco Volcanic Aerosols on South Polar Ozone Depletion in 2015

Abstract: The Southern Hemisphere Antarctic stratosphere experienced two noteworthy events in 2015: a significant injection of sulfur from the Calbuco volcanic eruption in Chile in April and a record‐large Antarctic ozone hole in October and November. Here we quantify Calbuco's influence on stratospheric ozone depletion in austral spring 2015 using observations and an Earth system model. We analyze ozonesondes, as well as data from the Microwave Limb Sounder. We employ the Community Earth System Model, version 1, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 60 publications
3
45
0
Order By: Relevance
“…This result is consistent with the location of the volcanic sulfuric acid aerosol layers around 16 km shown in CALIPSO and modeled backscatter figures (Figures ). This result is also consistent with Stone et al (), who found the volcanic aerosol enhances the ozone depletion particularly at 150–100 hPa and 55–68°S. Sunlight first causes ozone depletion near the edge of the vortex.…”
Section: Model Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with the location of the volcanic sulfuric acid aerosol layers around 16 km shown in CALIPSO and modeled backscatter figures (Figures ). This result is also consistent with Stone et al (), who found the volcanic aerosol enhances the ozone depletion particularly at 150–100 hPa and 55–68°S. Sunlight first causes ozone depletion near the edge of the vortex.…”
Section: Model Resultssupporting
confidence: 92%
“…In the remaining discussion, we will refer to this version of the model as Solomon et al (). Stone et al () found the simulated backscatter of the volcanic sulfate aerosol was consistent with the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations(CALIPSO) and found enhanced ozone depletion particularly at 150–100 hPa and 55–68°S. Ivy et al () found the enhanced ozone depletion was mostly caused by the volcanic aerosol, while the effect of dynamic or thermal feedbacks on ozone was minimal.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although OCS is the primary driver of the stratospheric aerosol during background periods (Sheng et al, ), even moderate volcanic eruptions, typically with a volcanic explosive index of three or four, can have a profound impact on aerosol levels (Vernier et al, ). The last two decades have been punctuated by several of these small‐to‐moderate eruptions and they have an important impact on climate, both through ozone depletion (Stone et al, ) and contributions to the radiative forcing (Solomon et al, ; Fyfe et al, ). The importance, as well as variability of the aerosol layer has meant that continuing measurements are of high importance for understanding the larger climate system.…”
Section: Introductionmentioning
confidence: 99%